Pribumisasi Islam Abdurrahman Wahid (Gus Dur): Pribumisasi Islam Abdurrahman Wahid (Gus Dur) - Shalahuddien, Ilham Akbar (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
The study of the indigenization of Islam from Abdurrahman Wahid's perspective is crucial for further in-depth study. This is because it is a subject of ongoing debate. The purpose of this paper is to understand three things: First, the form/paradigm The indigenization of Islam from Abdurrahman Wahid's perspective. Second, the internal and external factors that influence the indigenization of Islam from Abdurrahman Wahid's perspective. Third, the positive and negative impacts/implications of the indigenization of Islam from Abdurrahman Wahid's perspective on Indonesian society. The method used is Literature Research with an Article Review/Paper Review approach based on Harold Lasswell's theory, while data collection uses the Literature Review Procedure and is analyzed using the Content Analysis technique. The results found 3 things: First, there are 3 forms of paradigm: (1)socio-cultural(2) Islamic improvement with local culture(3) Pancasila Democracy Second, internally there are 3 factors that influence it: (1) Study abroad(2Family background and Islamic boarding school education(3Plural sociocultural environment There are 3 external factors that influence this: (1) social conditions(2) Political developments(3) The emergence of transnational Islamic movementsThird, there are 4 positive implications: (1)) Harmonization of religion and culture. (2) Increasing tolerance and harmony (3) Strengthening humanitarian values ​​(4) Strengthening the foundations of nationality. Meanwhile, there are 5 negative implications: (1) The emergence of accusations of syncretism (2) Rejection from certain groups (3) Misunderstanding of ideas (4)Concerns about the pluralization of Islamic identity(5) Potential conflict with the purification movement. The conclusion of this article shows that the indigenization of Islam from Abdurrahman Wahid's perspective is actually very complex, complete and comprehensive.Field SIslamic studies, Islamic socio-intellectual history, the indigenization of Islam (selected according to the field of science, whether macro, meso or micro)